Digital Literacy and Wise Language Use in Online Spaces: A Qualitative Study of Online Communities in Indonesia - Saputra, Dedi Gunawan; Stanislaus, Surip; Tu, Pham Anh; Husain, Desy Liliani; Setiawati, Rahmi (Journal International of Lingua and Technology, 2025)
The rapid growth of digital technologies has significantly transformed communication, particularly in online spaces where people engage in diverse forms of interaction. In Indonesia, online communities have become central to shaping public discourse and social norms. However, the increasing reliance on digital platforms raises concerns about digital literacy and the responsible use of language. This study explores the role of digital literacy and wise language use within online communities in Indonesia, focusing on how individuals navigate online interactions and the implications of their language practices. The aim of this research is to examine how members of online communities in Indonesia exhibit digital literacy and how they incorporate wise language use in their interactions. A qualitative research design, utilizing semi-structured interviews and content analysis of online communication, was employed to collect data from members of various online communities. The results revealed that while most participants demonstrated strong digital literacy skills, there was a notable variance in the application of wise language use. Some members employed respectful and thoughtful language, while others exhibited aggressive or harmful communication. In conclusion, this study highlights the importance of fostering both digital literacy and wise language use to improve the quality of online interactions. Recommendations for promoting these skills in online communities are discussed.